Green Tourism: Promoting Sustainable Practices for a Responsible Future - Ni Wayan Sumariadhi (Fakultas Dharma Duta UHN IGB Sugriwa Denpasar, 2023)
Research on green tourism highlights the significance of promoting sustainable practices within the tourism industry. The findings underscore the importance of sustainable tourism development, conservation initiatives, community involvement, policy frameworks, technological advancements, and consumer behavior in fostering a responsible and environmentally friendly tourism sector. The study used a mixed-methods approach is employed to capture both qualitative and quantitative data. This approach allows for a more comprehensive analysis by combining in-depth insights from interviews, surveys, and case studies with statistical data analysis and numerical measurements. In results, the research underscores the role of education, policy interventions, and technological advancements in advancing green tourism. By raising awareness among tourists, implementing robust regulations, and harnessing innovative technologies, the industry can mitigate its environmental impact, enhance resource efficiency, and improve the overall visitor experience.